Somatotopic organization of single primary afferent axon projections to cat spinal cord dorsal horn - Brown, PB (J Neurosci, 1991)
Horseradish peroxidase injection of identified low threshold cutaneous mechanoreceptor (LTCM) primary afferent axons was used to assess the somatotopic organization of hindlimb projections to laminae III and IV of cat dorsal horn. Multiple injections in the same animals were used to assess bilateral symmetry and precision. Thirty-one axons were injected, with more than 1 axon injected in each of 8 animals (25 axons). Somatotopic relations between their receptive field (RF) centers and the centers of their dorsal horn projections were similar to the somatotopic relations between dorsal horn cell RF centers and cell locations. Very few reversals of mediolateral somatotopic gradients (proximodistal RF location as a function of mediolateral projection center) were observed. Two afferents with nearly identical RFs in 1 animal had nearly identical projections. These observations held for many different combinations of receptor types. A simple mathematical model was used to demonstrate that assembly of dorsal horn cell RFs via passive sampling of the presynaptic neuropil by dorsal horn cell dendrites cannot account for the sizes of dorsal horn cell LTCM RFs. Hypothesized mechanisms for assembly of dorsal horn cell RFs must take into account the functional selectivity of connections required to produce RFs smaller than those predicted by the passive assembly model.